2018
DOI: 10.1093/nar/gky229
|View full text |Cite
|
Sign up to set email alerts
|

IGF2BP1 enhances an aggressive tumor cell phenotype by impairing miRNA-directed downregulation of oncogenic factors

Abstract: The oncofetal IGF2 mRNA binding proteins (IGF2BPs) are upregulated in most cancers but their paralogue-specific roles in tumor cells remain poorly understood. In a panel of five cancer-derived cell lines, IGF2BP1 shows highly conserved oncogenic potential. Consistently, the deletion of IGF2BP1 impairs the growth and metastasis of ovarian cancer-derived cells in nude mice. Gene expression analyses in ovarian cancer-derived cells reveal that the knockdown of IGF2BPs is associated with the downregulation of mRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
151
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(173 citation statements)
references
References 62 publications
21
151
1
Order By: Relevance
“…IGF2BP1 promotes tumor cell malignant phenotype by preferentially associating upstream of miRNA binding sites in the 3′ UTR of target mRNAs and then antagonizing miRNA-impaired gene expression [100]. Serum response factor (SRF) controls expression of oncogenes like FOXK1 and PDLIM7.…”
Section: Igf2bpsmentioning
confidence: 99%
See 1 more Smart Citation
“…IGF2BP1 promotes tumor cell malignant phenotype by preferentially associating upstream of miRNA binding sites in the 3′ UTR of target mRNAs and then antagonizing miRNA-impaired gene expression [100]. Serum response factor (SRF) controls expression of oncogenes like FOXK1 and PDLIM7.…”
Section: Igf2bpsmentioning
confidence: 99%
“…SRF contributes to tumor cell proliferation and metastasis, and transcription of oncogenes like FOXK1 and PDLIM7 [131,132]. IGF2BP1 enhances expression of SRF through inhibiting the miRNA-mediated degradation of it in an m6A-dependent way, resulting in increased expression of SRF, FOXK1 and PDLIM7 [78,100]. METTL3 stimulates AXL mRNA translation and epithelial-mesenchymal transition, thereby promoting growth and invasion of ovarian tumors [126,133].…”
Section: M6a Functions As a Tumor Promoter M6a Promotes Expression Ofmentioning
confidence: 99%
“…The currently best-understood IMP-mediated mechanism of modulating mRNA fate comprises the so-called safe-housing of specific transcripts in mRNP granules 4 . This "caging" of mRNAs ranges in its functional spectrum from packaging for cytoplasmic transport 5 , delayed translation within stable mRNPs [6][7][8] , cytoplasmic storage, and protection against pre-mature miRNA-directed mRNA regulation 3,[9][10][11][12] . Several target mRNAs have been suggested 3,13 , with IMP1 associating with the ACTB mRNA zipcode element and all three IMPs regulating HMGA2 stability via the 3´-UTR as the currently best-studied examples [9][10][11][12][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, increasing evidence suggested that the development of cancer cells involves the acquisition of stem‐cell‐like phenotypes and loss of differential features, which may lead to the progression and distant metastasis of cancer cells . Interestingly, we identified that LIN28A and IGF2BP1 , the essential members in stem cell maintenance, were also associated with advanced tumor stages in addition to the oncogenic effect in tumorigenesis . Thus, we proposed that the dysregulation of stemness‐related CT genes in TGCT may not only lead to the initiation of tumorigenesis and oncogenic de‐differentiation, but also contribute to the progression of testicular germ cells.…”
Section: Discussionmentioning
confidence: 90%
“…[23][24][25] Interestingly, we identified that LIN28A and IGF2BP1, the essential members in stem cell maintenance, were also associated with advanced tumor stages in addition to the oncogenic effect in tumorigenesis. 26,27 Thus, we proposed that the dysregulation of stemness-related CT genes in TGCT may not only lead to the initiation of tumorigenesis and oncogenic de-differentiation, but also contribute to the progression of testicular germ cells.…”
Section: Discussionmentioning
confidence: 99%